Forced Changes in the North Atlantic Storm Track Over the Last Millennium - O. Hess; R. Chemke (Geophysical Research Letters)
Abstract The North Atlantic storm track largely affects the regional weather and climate in Western Europe and the Eastern United States. While recent and projected changes in the storm track due to human emissions have been extensively studied, the storms' response to natural forcings in past centuries is largely unknown. Using climate model simulations of the pre‐industrial millennium, we find that natural forcings acted to intensify the summer storm track over multi‐centennial timescales, with minor impacts on the winter storm track. In contrast to the human‐induced larger warming of high latitudes relative to low latitudes, which has weakened the summer storm track, natural agents cooled high latitudes more, enhancing the meridional temperature gradient, which intensified the storm track. This study highlights the unprecedented impacts of human emissions relative to the last millennium's natural forcing agents and the importance of including natural forcings in model projections.